Professional Realism in the Legal Translation Classroom: Translation Competence and Translator Competence - Biel, Łucja (Meta, 2011)
The paper proposes how to integrate professional realism in BA legal translation classes at the level of translation competence and translator competence. The distinction between competences is adopted from Kiraly, where the former means the ability to translate to the required standard while the latter is the ability to function efficiently as a professional. The competences are developed concurrently, the main focus being placed on translation competence. Professional realism is ensured in content design (the most frequently translated branches of law), a varied selection of authentic and prototypical texts, an eclectic teaching approach progressing from task-based learning to project-based learning, including subject-field competence building, terminology work and, finally, translation and revision projects which integrate all tasks and activities in a single assignment.